Effect Of Corner On Evacuation Behaviour During Building Egress By Using Dem-Based Multi Agent Model - Kasehyani, Nur Hanis (Universiti Sains Malaysia, 2017)
This thesis focuses on the effect of corner on evacuation behaviour during building egress. The case study is conducted at Pusat Pengajian Kejuruteraan Awam (PPKA). The objectives of this study were to quantify the capacity of corner, determine numerically the threshold density near the corner during building egress and determine the critical width related to different density of pedestrian. Simulation of hypothetical evacuation scenarios at corner was carried out based on different pedestrian density and different widths. The main parameters of this study are the pedestrian density and width of corner. A total of 27 simulations had been performed on the trial domain with three different width and nine different pedestrian density. Crowd Behaviour Simulator for Disaster Evacuation (CBS-DE) with the additional tool called Human Behaviour Simulator (HBS) was used to analyse the evacuation behaviour. The results of the simulations were egress time and interaction force. The findings show that there are no series of jamming and clogging that indicate the threshold density since the pedestrian density may be not sufficient to cause jamming and clogging. Meanwhile, Inter-9 shows the best time series of the maximum interaction force graph with pattern of increasing maximum interaction force as the corridor width decreases and the interaction force did not exceed the upper and lower limit of contact force. From the case study, it is found that the alternative evacuation route can improve the evacuation process at the ground floor of PPKA.